Rekonstruksi Aksin Wijaya atas Interpretasi Qs. an-Nisa’ [4]: 1 Sebuah Kritik atas Penafsiran Tekstualis Normatif dan Kontekstualis Progresif - Haitomi, Faisal (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2021)
Some scholars say that the biased interpretation of religion has contributed greatly to the gender discrimination that has occurred over the last few decades. Understanding of Qs. an-Nisa' [4]: 1 regarding the beginning of creation is alleged to be the starting point for discrimination in the name of gender. There are groups who are always at odds in understanding this verse, the first is the normative group which thinks that Eve was created from Adam's rib, while the rational group thinks that Eve was not created from Adam's rib but from one kind (nafsun wahidah). But on the other hand, Aksin Wijaya denied the two groups, because according to him the two groups had misunderstood the spirit of the verse. The method used in this paper is library research with historical analysis as the approach used. This research concludes that human social status is not determined by gender, but by devotion to God. Because in Qs. an-Nisa' [4]: 1 the right emphasis is not on the sentence "nafsun wahidah" but on the sentence "ittaqullah". Because this verse was revealed in Medina even though it is linguistically categorized as a Meccan verse because it uses the initial redaski "ya ayyuhan nas".